1998
DOI: 10.1209/epl/i1998-00322-3
|View full text |Cite
|
Sign up to set email alerts
|

Competing exchange interactions in Li 2 CuO 2

Abstract: The dispersion of the spin-waves in single crystals of Li2CuO2 has been investigated by means of inelastic neutron scattering. The results yield a single spin-wave branch characterized by a large gap ∆ = 1.4 meV at the zone centre due to easy-axis uniaxial anisotropy. Linear spin-wave theory is used to obtain the exchange integrals in this material. It turns out that the nearest-neighbor exchange interactions in the basal plane are antiferromagnetic leading to frustration between the magnetic moments. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
67
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 11 publications
11
67
3
Order By: Relevance
“…Our calculated values for J 1 and J 2 are larger than the ones derived from experiment by Boehm et al [12] and also somewhat larger than the 1.3 -2.6 meV estimated for J 1 by fitting high temperature specific heat data [29], but are of the same order of magnitude as the ones calculated by Mizuno et al [11]. Again, we stress that, although the values are of the same order, the explicit inclusion of the Li ions gives rise to important changes in the ratio of J 1 and J 2 .…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…Our calculated values for J 1 and J 2 are larger than the ones derived from experiment by Boehm et al [12] and also somewhat larger than the 1.3 -2.6 meV estimated for J 1 by fitting high temperature specific heat data [29], but are of the same order of magnitude as the ones calculated by Mizuno et al [11]. Again, we stress that, although the values are of the same order, the explicit inclusion of the Li ions gives rise to important changes in the ratio of J 1 and J 2 .…”
Section: Resultscontrasting
confidence: 94%
“…However, several articles have been published that consider the magnitude of these couplings and very surprising conclusions were drawn. It is suggested that J 1 is not necessarily ferromagnetic because of the not exactly rectan-gular Cu-O-Cu angle, which is in fact 94° [10][11][12]. Mizuno et al [11] derive from a three band Hubbard model that the second neighbour interaction (J 2 ) is about 60% of J 1 and Weht and Pickett [13] report that J 1 is even larger than J 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it turns out that this reduction does not concern the anisotropic corrections to H iso . This is for example justified by the observation of a very large spin-wave gap in Li 2 CuO 4 [3] [5,6]. The subject of the present paper, LiCuVO 4 , exhibits Cu chains comparable to CuGeO 3 and to the other Cu oxides mentioned above, but it has been discussed controversially as one-or two-dimensional antiferromagnet [8,9].…”
supporting
confidence: 51%
“…by the crystal field [3][4][5][6]. Indeed, the magnetic anisotropy due to the orbital degrees of freedom plays a minor role in the two-dimensional cuprates, such as the parent compound of the high-T c superconductors La 2 CuO 4 .…”
mentioning
confidence: 99%